Problems of appropriation of rental income society - Janshanlo, R (Journal of Economic Research & Business Administration, 2016)
The question of equitable distribution and assignment of rental incomeshould be viewed with the possibility of its most efficient use in thepublic interest. The rent is by far one of the sources of economic growthand leverage. The proposed conceptual statements involve enhancing therole of the state in relation to rental industries.